Bioassay Guided Isolation of Free Radical Scavenging Agent from the Bark of Bridelia retusa - Sharma, Khaga Raj; Adhikari, Achyut; Choudhary, M. Iqbal; Awale, Suresh; Kalauni, Surya Kant (Journal of Institute of Science and Technology, 2015)
Bioassay guided fractionation of ethyl acetate soluble fraction of methanolic extract of Bridelia retusa yielded tambulin (1), beta-sitosterol (2), and beta-sitosterol glucoside (3), and their structures were elucidated using modern spectroscopic techniques. Compounds 1-3 were evaluated for their antioxidant activity and compound 1 was found to be potent antioxidant. The DPPH assay showed that the compound 1 has potent antioxidant activity with IC50 166.15±1.92 SEM [muM] and the radical scavenging activity was found to be 86.03% where as the standard butylated hydroxy toluene (BHT) has IC50 value 128.83±2.1 SEM [muM]. The radical scavenging activity of standard butylated hydroxy toluene was about 86% .The total phenolic content in ethyl acetate soluble fraction was found to be 147.20±1.5 mg GAE/gm and the total flavonoid content was found to be 16.64±0.00 mg QE/gm. Journal of Institute of Science and Technology, 2015, 20(1): 97-101